Relationship between Knowledge and Personal Hygiene Behavior during Menstruation in Adolescents at the Aisyiyah Orphanage, Pekanbaru City - Rizka Angrainy; Lidia Fitri; Aprilia Utari (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2021)
One thing that must be considered during menstruation is personal hygiene and the impact of personal hygiene during menstruation is vaginal discharge. The purpose of the study was to analyze the relationship between knowledge and personal hygiene behavior during menstruation in adolescents. The population in this study were 35 young women. Sampling in this study total population technique (total sampling) with a total sample of 35 respondents. Data using univariate and bivariate Chi Square tests, obtained the results of having sufficient knowledge and positive behavior in performing Personal Hygiene During Menstruation, namely 15 respondents (65.2%). Statistical test results obtained p value 0.196 > 0.005, which means there is no relationship between the level of knowledge and the behavior of adolescent girls about personal hygiene during menstruation. Therefore, it is hoped that here there will be cooperation between health workers and the orphanage, especially in terms of providing complete information at the Aisyiyah Orphanage